Determinants of Prolanis Utilization in Diabetes Mellitus Patients as a Chronic Disease Management Program - Shofiyana Shofiyana; Sutopo Patria Jati; Farid Agushybana (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Diabetes mellitus (DM) has emerged as a global public health problem due to its complications and associated mortality. Diabetes management has been legalized in Indonesia under the Chronic Disease Management Program (Prolanis), with BPJS Kesehatan as the coordinating entity. Despite the availability of Prolanis, participation appears to be limited, and patient interest varies significantly. This study aimed to identify the determinants influencing Prolanis consumption among diabetes mellitus patients. This study utilized an analytical observational methodology with a cross-sectional design, focusing on patients with diabetes mellitus (DM) enrolled in the Prolanis program at various Primary Health Care Facilities (FKTP) in Demak Regency. The research encompassed 120 participants chosen via proportionate stratified random sampling. Data were collected via a structured questionnaire that had been subjected to validity and reliability assessments. The independent variables were categorized into high and low groups based on the median value of each variable. The utilization of the Prolanis program was characterized by the consistent engagement of patients in scheduled program activities during the past three months. The data analysis included descriptive statistics, chi-square tests to assess bivariate relationships, and multivariable logistic regression to determine characteristics that independently affected program utilization. The bivariate analysis indicated that knowledge, familial support, assistance from healthcare providers, accessibility of services, and perceived necessity were substantially correlated with participation in Prolanis activities (p<0.001). Subsequent study employing multivariable logistic regression revealed that all variables continued to be significant predictors of program usage (p<0.05). Among these characteristics, family support had the most significant influence (Exp(B)=11.2), succeeded by knowledge (10.5), accessibility of resources (10.4), perceived need (8.1), and healthcare professional support (6.8). The regression model accounted for 80.6% of the variance in Prolanis consumption, as evidenced by a Nagelkerke R² score of 0.806. The results indicate that robust family engagement and adequate patient information significantly influence participation in Prolanis activities. Initiatives to enhance program usage among persons with diabetes mellitus should concentrate on bolstering family involvement, broadening patient education, and facilitating improved access to healthcare services. Keywords: Prolanis, DM, Family Support, Knowledge, Service Accessibility.